Serum autotaxin is a prognostic indicator of liver-related events in patients with non-alcoholic fatty liver disease - Takanobu Iwadare; Takefumi Kimura; Taiki Okumura; Shun-ichi Wakabayashi; Taro Nakajima; Shohei Kondo; Hiroyuki Kobayashi; Yuki Yamashita; Ayumi Sugiura; Naoyuki Fujimori; Tomoo Yamazaki; Hideo Kunimoto; et al. (Communications Medicine, 2024)
Abstract Background Circulating autotaxin (ATX) levels have been reported to correlate with liver inflammation activity and liver fibrosis severity in patients with non-alcoholic fatty liver disease (NAFLD). The objective of this study is to investigate whether serum ATX could predict liver-related events (LRE) in NAFLD patients. Methods This retrospective investigation includes 309 biopsy-proven NAFLD patients registered at Shinshu University Hospital. All patients are followed for at least 1 year, during which time the prevalence of LRE, including newly developing hepatocellular carcinoma, hepatic encephalopathy, ascites, and esophagogastric varices, is investigated in relation to ATX levels at the time of liver biopsy. Results During the median follow-up period of 7.0 years, LRE are observed in 20 patients (6.5%). The area under the receiver operating characteristic curve and cut-off value of serum ATX for predicting LRE are 0.81 and 1.227 mg/l, respectively. Multivariate Cox proportional hazards models for LRE determine ATX and advanced fibrosis as independently associated factors. Furthermore, in a competing risk analysis that considered non-liver-related death as a competing event, ATX (HR 2.29, 95% CI 1.22–4.30, p = 0.010) is identified as an independent factor associated with LRE, along with advanced fibrosis (HR 8.01, 95% CI 2.10–30.60, p = 0.002). The predictive utility of ATX for LRE is validated in an independent cohort. Conclusions Serum ATX may serve as a predictive marker for LRE in patients with NAFLD.